CD24 knockout prevents colorectal cancer in chemically induced colon carcinogenesis and in APCMin/CD24 double knockout transgenic mice. Issue 5 (21st March 2014) - Naumov, Inna; Zilberberg, Alona; Shapira, Shiran; Avivi, Doran; Kazanov, Dina; Rosin‐Arbesfeld, Rina; Arber, Nadir; Kraus, Sarah
<x xml:space="preserve">Abstract</x> Increased expression of CD24 is seen in a large variety of solid tumors, including up to 90% of gastrointestinal (GI) tumors. Stable derivatives of SW480 colorectal cancer (CRC) cells that overexpress CD24 proliferate faster, and increase cell motility, saturation density, plating efficiency, and growth in soft agar. They also produce larger tumors in nude mice as compared to the parental SW480 cells. Most significantly, even depletion of one copy of the CD24 allele in the APCMin/+ mice of a transgenic mouse model led to a dramatic reduction in tumor burden in all sections of the small intestine. Homozygous deletion of both CD24 alleles resulted in complete abolishment of tumor formation. Moreover, CD24 knockout mice exhibited resistance to chemically induced inflammation‐associated CRC. Finally, a new signal transduction pathway is suggested: namely, CD24 expression downstream to COX2 and PGE2 synthesis, which is directly regulated by β‐catenin. CD24 is shown in vitro and in vivo as being an important oncogene in the gut, and one that plays a critical role in the initiation and progression of carcinogenesis.